Risk of Poststroke Dementia in Patients With and Without Atrial Fibrillation: A Nationwide Cohort Study - Sigrid Breinholt Vestergaard; Jakob Nebeling Hedegaard; Christina C. Dahm; Hanne Gottrup; Søren P. Johnsen; Grethe Andersen; Janne Kærgård Mortensen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atrial fibrillation (AF) is associated with an increased risk of dementia in nonstroke populations. We aimed to study whether AF was also associated with an increased risk of poststroke dementia (PSD). Methods This nationwide register‐based cohort study included all patients with incident acute ischemic stroke (AIS) in Denmark from 2008 to 2017. Patients with AF were compared with patients without AF using propensity‐score weighting. The primary outcome was PSD, determined as a diagnosis of dementia or use of dementia medication within 5 years from AIS. PSD hazard rates were compared between patients with and without AF using Cox proportional hazards regression. Dementia‐free mortality risk was evaluated as a secondary outcome. Results We included 61 058 patients with incident AIS, 12 248 with AF, and 48 810 without AF. Mean±SD age was 70.5±11.6, and 56.1% were men. A total of 3190 patients were diagnosed with dementia within a median of 2.1 (interquartile range, 0.82–4.2) years after AIS. In the unadjusted analysis, patients with AF had a higher PSD rate than patients without AF (19.0/1000 person‐years versus 11.5/1000 person‐years; hazard ratio [HR], 1.63 [95% CI, 1.51–1.77]). After adjustment for confounding factors, PSD risk was comparable between patients with and without AF (HR, 1.07 [95% CI, 0.97–1.17]). Dementia‐free mortality risk was higher for patients with AF than patients without in both unadjusted (HR, 2.14 [95% CI, 2.07–2.21]) and adjusted analyses (HR, 1.31 [95% CI, 1.26–1.37]). Conclusions Among patients with AIS, AF was not associated with an increased risk of PSD, likely due to an increased mortality risk. Patients with AF may not be a particular PSD high‐risk group.